Governance Network in Food Security Policy: a Study of the Lorong Wisata Program in Makassar City - Syaputra, Much Faisal (Jurnal Administrasi dan Kebijakan Publik, 2025)
Makassar, Indonesia’s fourth-largest city, faces escalating food security challenges amid rapid urbanization, prompting the municipal government to introduce the Lorong Wisata program, which integrates urban farming to enhance local food self-sufficiency. This study critically examines the governance structure of the program’s governance network, focusing on network configuration, coordination mechanisms, and power relations among actors. Employing a qualitative case study guided by Klijn and Koppenjan’s governance network framework, data were collected through semi-structured interviews, field observations, and document analysis, then analyzed using thematic coding and inductive actor mapping. The findings reveal a fragmented governance network dominated by the municipal government’s vertical authority, with weak cross-sectoral collaborationparticularly with universities and private actors. Institutional fragility is reflected in the absence of functional task forces and technical teams mandated by local regulations, resulting in symbolic rather than substantive coordination. The study concludes that formal multi-actor designs remain limited in contexts shaped by state-centric governance logics, as symbolic coordination and fragmented trust constrain the transformative potential of community-based food initiatives. Strengthening inclusive partnerships, rebuilding trust, and fostering deliberative coordination are essential to advancing sustainable urban food security governance.